2020
DOI: 10.2147/rmhp.s250741
|View full text |Cite
|
Sign up to set email alerts
|

<p>Nurses’ Attitudes and Knowledge of Peripherally Inserted Central Catheter Maintenance in Primary Hospitals in China: A Cross-Sectional Survey</p>

Abstract: Background and Aim: The promotion of peripherally inserted central catheter (PICC) maintenance in primary hospitals can benefit discharged patients with PICCs living in remote areas a lot. Yet, no primary hospitals had introduced PICC maintenance technology in Hunan province, China. The present study aimed to evaluate nurses' attitudes and knowledge of PICC maintenance in primary hospitals in Hunan province, China. Materials and Methods: From November 2018 to January 2019, a total of 560 nurses from 28 communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 27 publications
2
17
0
1
Order By: Relevance
“… 12 Besides, our previous study found that hospitals with a higher level usually provide more professional nursing skills training so that nurses’ professional operation skills and confidence in specialized nursing operations can be improved. 16 It is recommended that government unify the Internet +home care service platform and rationally allocate service contents according to the willingness of nurses at different levels of hospitals to optimize the allocation of medical and nursing resources. At the same time, hospitals and nursing colleges should strengthen home-based nursing operation skills training and enhance operation ability.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Besides, our previous study found that hospitals with a higher level usually provide more professional nursing skills training so that nurses’ professional operation skills and confidence in specialized nursing operations can be improved. 16 It is recommended that government unify the Internet +home care service platform and rationally allocate service contents according to the willingness of nurses at different levels of hospitals to optimize the allocation of medical and nursing resources. At the same time, hospitals and nursing colleges should strengthen home-based nursing operation skills training and enhance operation ability.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that give more material, financial, and policy support to secondary and lower-level hospitals from the government level. 8 On the other hand, due to the large gap in medical resources and technical levels between different cities and regions, it is suggested that tertiary hospitals can play a leading role, and “Internet + care” be used to set up online and offline training mechanisms. 38 We can communicate and exchange experiences with each other, improving clinical nurses’ cognitive rate of CRT and narrowing the gap in understanding CRT in regional medical institutions.…”
Section: Discussionmentioning
confidence: 99%
“… 28 , 29 The higher the professional title and more training times, the higher the score of nurses on CRT knowledge, attitude, and practice, which is similar to the previous study. 8 , 39 Research shows that nurses with more training times have higher scores on cognition and nursing of thrombus around indwelling venous catheter than nurses with fewer training times. 29 And The better you understand the importance of CRT prevention and treatment through CRT training, your corresponding CRT practice is more active.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The topic of specific skills for PICC handling, insertion, and maintenance was much discussed. Nurses considered that training was fundamental for the adoption of this medical device, as addressed in previous studies with nurses [ 29 ]. As fewer patients needed a PICC than those needing a PVC in the study setting, its incorporation into nursing practices was a limitation.…”
Section: Discussionmentioning
confidence: 99%